Possession, alterity, modernity - Malik, Aditya (Religion and modernity in India, 2017)
This densely theoretical chapter looks at the ritual of possession as practiced in the Central Himalayas to interrogate the assumptions of modernity as a liberating force that ensures freedom from religion. Survival of such rituals, he argues, is a reminder of the past that modernity is supposed to have displaced. The fact that it is continually thriving even in the present time shocks and challenges the foundations of the modern nation-state based on the notions of science, technology, and rationality and compels us to rethink the modern ideas of agency and subjectivity.